2004
DOI: 10.1002/eji.200324745
|View full text |Cite
|
Sign up to set email alerts
|

CCR4‐deficient mice show prolonged graft survival in a chronic cardiac transplant rejection model

Abstract: Chronic graft rejection mediated by cellular immune responses still poses a serious clinical problem in transplant surgery. Chemokines coordinate the recruitment of leukocytes in inflammatory and immune responses. Their precise functions in the rejection of allografts are still ill defined. This study investigates the role of chemokine receptor 4 (CCR4) in acute and chronic cardiac allograft rejection in mice. Allogeneic hearts were transplanted into CCR4 deficient (CCR4 -/-) and control recipients. Reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
(64 reference statements)
2
25
0
Order By: Relevance
“…Studies previous to ours suggested that the innate immune response in CCR4 Ϫ/Ϫ mice was altered in that these mice were dramatically less susceptible to the development of lipopolysaccharide-induced endotoxic shock (22). More recently, CCR4 Ϫ/Ϫ mice showed prolonged cardiac allograft survival compared with their wild-type counterparts (33). Given that previous reports have suggested that CCL17 can bind and signal through CCR8 (8,36), the development of invasive pulmonary aspergillosis was also examined in CCR8 Ϫ/Ϫ mice.…”
Section: Discusssionmentioning
confidence: 53%
“…Studies previous to ours suggested that the innate immune response in CCR4 Ϫ/Ϫ mice was altered in that these mice were dramatically less susceptible to the development of lipopolysaccharide-induced endotoxic shock (22). More recently, CCR4 Ϫ/Ϫ mice showed prolonged cardiac allograft survival compared with their wild-type counterparts (33). Given that previous reports have suggested that CCL17 can bind and signal through CCR8 (8,36), the development of invasive pulmonary aspergillosis was also examined in CCR8 Ϫ/Ϫ mice.…”
Section: Discusssionmentioning
confidence: 53%
“…In contrast, Treg recruitment was less pronounced and not altered in Ccl17 E/E Apoe -/-mice. Nevertheless, the inflammatory recruit- (25), lymphocyte and CD4 + T cell recruitment was unaltered in various in vivo models, e.g., OVA-induced airway inflammation, cardiac allograft rejection, and skin inflammation related to atopic dermatitis in Ccr4 -/-mice (36)(37)(38). Notably, we found increased Treg accumulation in aortas of Ccl17 E/E Apoe -/-mice and in LNs of Ccl17-deficient mice.…”
Section: Discussionmentioning
confidence: 71%
“…Inhibition of CCR4 and its ligands led to an increase in heart graft survival associated with a decreased in DC/T-cell interactions and an inhibition of monocytes and NK cells present in the graft (Alferink et al 2003;Huser et al 2005). Last, CCR7 is known to be involved in the localization of both DCs and T cells in the T-cell-rich zones of the LNs, indicating a role for CCR7 in T-cell homing and priming (Hopken et al 2004).…”
Section: Chemokinesmentioning
confidence: 99%